Analysis of success factors in advertising - Fedorchak, Oleksiy; Kedebecz, Kristina (Видавництво Львівської політехніки, 2017)
The essence of factors of the success of advertising campaigns is investigated. The stages of conducting and stages of evaluation of the effectiveness of advertising campaigns are determined. Also defined goals and objectives of advertising campaigns.
Keywords: advertising campaign; marketing; efficiency; trade; communication